Current Population Survey, July 2014 (United States): Tobacco Use Supplement (TUS) ([Verlag nicht ermittelbar], 2018)
The Current Population Survey Tobacco Use Supplement data collection from July 2015 is comprised of responses from two sets of survey questionnaires, the basic Current Population Survey (CPS) and a Tobacco Use Supplement (TUS) survey. The TUS 2014-2015 Wave consists of three collections: July 2014, January 2015, and May 2015. The CPS, administered monthly, is the source of the official government statistics on employment and unemployment. From time to time, additional questions are included on health, education, and previous work experience. The Tobacco Use Supplement to the CPS is a National Cancer Institute sponsored survey of tobacco use that has been administered as part of the US Census Bureau's CPS approximately every 3-4 years since 1992-1993. Similar to other CPS supplements, the Tobacco Use Supplement was designed for both proxy and self-respondents. All CPS household members age 18 and older who completed CPS core items in July 2014 were eligible for the supplement items. A new feature for the 2014-2015 cycle included random selection of self-interviewed respondents in larger households to reduce respondent burden. If the household had only 1 supplement eligible member then that person was selected for self-interview. If the household had only 2 supplement eligible members, then both of them were selected for self-interview. If the household had 3 or 4 supplement eligible members, then 2 of them were randomly selected for self-interview and the remaining were interviewed by proxy. If the household had more than 4 supplement eligible members, then 3 of them were randomly selected for self-interview and the rest of the eligible respondents were interviewed by proxy. Those selected for self-interview were eligible for the entire supplement, whereas proxy respondents were only eligible for an abbreviated interview. Occasionally, those persons to be interviewed by proxy, if available for self-interview, were interviewed directly but asked the abbreviated proxy path questions. Both proxy and self-respondents were asked about their smoking status and the use of other tobacco products. For self-respondents only, different questions were asked depending on their tobacco use status: for former/current smokers, questions were asked about type of cigarettes smoked, measures of addiction, attempts to quit smoking, methods and treatments used to quit smoking, and if they were planning to quit in the future. All self-respondents were asked about smoking policy at their work place and their attitudes towards smoking in different locations. Demographic information within this collection includes age, sex, race, Hispanic origin, marital status, veteran status, immigration status, educational background, employment status, occupation, and income.